Association of the stress hyperglycemia ratio and clinical outcomes in patients with stroke: A systematic review and meta-analysis - Huang, Yong-Wei; Yin, Xiao-Shuang; Li, Zong-Ping (Frontiers in Neurology, 2022)
OBJECTIVE: Stress hyperglycemia (SH) is common in patients with acute disease such as stroke. Stress hyperglycemia ratio (SHR), calculated by glucose/glycated hemoglobin, has been developed for assessing SH. We performed a systematic review and meta-analysis aiming to investigate the association between SHR and clinical outcomes in stroke patients.METHODS: A comprehensive literature search of the PubMed, Embase, Cochrane Library databases, Clinicaltrials.gov and WHO-ICTRP was performed. The end points of poor outcome, mortality, neurological deficit, hemorrhagic transformation (HT), and infectious complications were statistically analyzed.RESULTS: Sixteen retrospective studies met the eligibility criteria, and a total of 183588 patients were included. The meta-analysis demonstrated a significant increase in the incidence of poor outcome, according to assessment by the modified Rankin Scale (mRS) ≥ 3 points (odds ratio[OR] 2.53, 95% confidence interval [CI] 1.99-3.22, P < 0.00001, I2 = 68%), mortality (OR 1.96, 95% CI 1.58-2.44, P < 0.00001, I2 = 61%), neurological deficit (OR 1.99, 95% CI 1.47-2.70, P < 0.00001, I2 = 75%), hemorrhagic transformation (HT) (OR 3.70, 95% CI 2.69-5.08, P < 0.00001, I2 = 0%), and infectious complications ([Pneumonia] OR 2.06, 95% CI 1.57-2.72, P < 0.00001, I2 = 24%; [Urinary tract infection] OR 2.53, 95% CI 1.45-4.42, P = 0.001, I2 = 57%) in stroke patients with higher SHR. However, no significant influence was observed for recanalization rate (OR 0.86, 95% CI 0.54-1.38, P = 0.53, I2 = 0%).CONCLUSIONS: With or without diabetes, no matter undergoing the intravenous thrombolysis or mechanical thrombectomy, higher SHR significantly increased the occurrence of poor outcome, mortality, neurological deficit, HT and infectious complications. No statistically significant difference of recanalization was observed between the two groups. More attention must be paid in clinical practice about SH. Future investigation should focus on the diagnostic value of SHR and the early control of hyperglycemia. Meanwhile, whether SHR could be a novel target for early intervention is worthy of attention in future research. Besides, the impact of the dynamic change of glucose-to-HbA1c ratio on ICH outcomes requires further investigation in future research. The available massive sample studies reflect the actual situation in the clinic and assist clinical decision makers.